Endogenous modulation of delta phase by expectation–A replication of Stefanics et al., 2010. (April 2022) - Herbst, Sophie K.; Stefanics, Gabor; Obleser, Jonas
Abstract: The human brain efficiently extracts the temporal statistics of sensory environments and automatically generates expectations about future events. An influential Hypothesis holds that these expectations can find their implementation in neural oscillations, notably in the delta band (.5–3 Hz). Rhythmic fluctuations of cortical excitement are thought to align and match up in phase to the temporal structure of the sensory environment. This alignment is thought to result in the more excitable phase range of neural oscillations to overlap with the predicted onset of sensory events which in turn results in more efficient processing of sensory input, especially so in audition. An unresolved issue concerns whether such phase-aligned rhythmic brain activity is driven exclusively by the exogenous temporal structure of the input, or whether it also reflects phase re-alignment due to endogenous expectations based on stimulus probability and task relevance. In a seminal study, Stefanics et al. (2010) presented stimuli in a rhythmic stream and observed that delta phase consistency across trials was modulated by endogenous target onset expectations: delta phase consistency was higher prior to more probable (strongly expected) compared to less probable (weakly expected) target onsets. The present study replicates Experiment II of the original study, most importantly the modulation of delta phase consistency by endogenous expectations, and underlines a direct relationship between phase locking and behaviour. Our additional analyses locate the sources of the delta phase-alignment to motor, pre-motor, parietal, and temporal areas, and provide evidence for an ongoing delta oscillation, in line with the interpretation of oscillatory phase alignment rather than a transient evoked response. Importantly, this work shows that the phase of delta oscillations can be modulated by top-down control, and hence qualifies as a potential mechanism for the neural implementation of (rhythmic) temporal predictions.